(untitled) (Journal of Computational Mathematics, 1997)
The paper discusses H-splitting and H-compatible splitting, furthermore, some properties are given. Asynchronous parallel multisplitting algorithm and its generalization for linear systems Ax=b are established. Convergence of these algorithms is proved under given conditions. The convergent range of relaxation factor ω is given, numerical example is shown.